The European hare as a hidden challenge for forest regeneration: common protection measures are ineffective - Skoták, Vlastimil; Cukor, Jan; Linda, Rostislav; Vacek, Zdeněk (Frontiers in Forests and Global Change, 2025)
Forest management in Central Europe is affected by numerous biotic and abiotic factors, and wildlife damage to forest stands is one of the major ones. While damage to young forest stands is predominantly attributed to wild ungulates, the potential negative impact of the European hare (Lepus europaeus) on tree plantations has been largely overlooked. Therefore, this study aimed to quantify hare damage in comparison with ungulates, determine which developmental stages of trees are most attractive to hares, compare browsing preferences among key commercial species, and assess the effectiveness of commonly used protection measures. We evaluated 209 calamity clearcuts with 75,912 seedlings to determine the proportion and structure of browsing damage. Research revealed a substantial proportional damage caused by the European hare, accounting for 10.12%, while wild ungulates were responsible for 7.11% of browsing damage. The species distribution played a crucial role in the damage rate. Hares caused the greatest browsing damage on silver birch (Betula pendula—37%), while ungulates preferred Scots pine (Pinus sylvestris—29%). Moreover, browsing intensity caused by hares was seasonally affected with a significantly higher damage ratio in autumn (<14%) compared to the spring season (<2%) when clearcuts offer enough alternative fodder opportunities. Common protection measures, such as coating and fencing, proved largely ineffective against hare browsing. Surprisingly, sycamore maple (Acer pseudoplatanus) and European beech (Fagus sylvatica) were more heavily damaged by hares when coated than unprotected seedlings. The results showed that the European hare plays a crucial role in clear-cut reforestation, highlighting the need for enhanced focus on protective measures, including population management and the use of specialized fencing made of dense wire mesh compared to the usual protection against wild ungulates.